A 24-week multi-component exercise program improves cognition and body composition in older adults with mild cognitive impairment: a randomized controlled trial - Xu, Danming; Wu, Xiaochu; Dai, Junming; Li, Qing; Wang, Zhi; Huang, Yimin; Zhang, Yu; Cao, Junjie; Li, Bingxue; Dong, Yirong; Tu, Yanhao (Frontiers in Aging Neuroscience, 2026)
BackgroundThis study investigated whether a 24-week, community-based multicomponent exercise intervention (MCEI) can improve body composition and cognitive function in older adults with mild cognitive impairment (MCI).MethodsIn this single-center, parallel-group randomized controlled trial (RCT), 64 community-dwelling adults aged 65–75 years with MCI characterized by Mini-Mental State Examination (MMSE) ≥ 24, Montreal Cognitive Assessment (MoCA) ≤ 26, Clinical Dementia Rating (CDR) = 0.5, low skeletal muscle mass were randomly allocated (1:1) to a MCEI (aerobic, resistance and balance training, 3 × 60 min/week) or to a usual-activity control (UAC) group receiving weekly health education. Primary outcomes were skeletal muscle mass (SMM), fat-mass index (FMI), MMSE and MoCA; secondary outcomes included skeletal muscle index (SMI), basal metabolic rate (BMR), Instrumental Activities of Daily Living (IADL) and Animal Fluency Test (AFT). Assessments were conducted at baseline and within 1 week post-intervention by trained, blinded assessors. Intervention effects were examined with a 2 (group) × 2 (time) repeated-measures analysis of variance (ANOVA), reporting partial eta-squared (η2) as the effect-size estimate.ResultsA significant Group × Time interaction was observed for SMM (p < 0.001, η2 = 0.195) and FMI (p = 0.003, η2 = 0.153), indicating differential changes between groups; with significant improvements observed only in the MCEI group. SMI showed no significant interaction effect (p = 0.270, η2 = 0.021), whereas no significant interactions were found for MMSE, MoCA, or AFT (p ≥ 0.18, η2 ≤ 0.03).ConclusionA 24-week community-based multicomponent exercise program safely increased skeletal muscle mass and reduced fat mass in older adults with MCI, but did not produce measurable improvements on screening-level cognitive measures. Future studies with longer duration, larger samples, and inclusion of cognitive challenges are warranted to clarify exercise–cognition interactions and establish dose–response relationships for both body composition and domain-specific cognition.Clinical trial registrationIdentifier ChiCTR2000035012.